The Effect of Human Resource Management on Learning Effectiveness in Vocational Schools - Desmiarni Desmiarni; Hasan Maksum; Wawan Purwanto (Journal on Education, 2024)
This study aims to analyze the effect of human resource management (HRM) on the effectiveness of learning in vocational schools. This research uses quantitative methods with a meta-analysis approach. The data source came from an analysis of 10 national and international journals. The data collection process is through searching the google database, ProQuest and ScienceDirect. Data analysis techniques in quantitative analysis research by calculating the value of effect size with the help of the JSAP application. The results of this study concluded that human resource management has a significant influence on the effectiveness of learning in vocational schools with an effect size value of 0.814; P< 0.001. The findings have a positive impact on vocational school teachers to provide professional and competent teacher candidates in work. Vocational schools need to implement good HR practices to improve the quality of education and produce job-ready graduates.